Essays on Fiscal Policy and Tax Compliance - Small, Oronde D (2017)
This dissertation comprises three essays that examine critical aspects of fiscal policy and explores important determinants of tax compliance in a developing country context. The first essay examines the fiscal response to changes in debt-to-GDP for a panel of developing countries. Our empirical strategy adopts a dynamic difference generalized methods of moments (DGMM) model with forward orthogonal deviation. We find a positive and significant response for the primary balance and ‘fiscal effort’ to changes in debt-to-GDP. For the fiscal components, we find a positive relationship between debt-to-GDP and general and tax revenues, and a negative relationship with primary spending. We also find evidence of nonlinearities, with countries making larger increases in the primary balance and fiscal effort at higher levels of debt, largely driven by increases in revenues. Higher income countries demonstrate a greater propensity to adjust along the revenue margins, compared to lower income countries. This might be indicative of systemic revenue mobilization challenges facing the latter. The second essay examines the effect of the provision of taxpayer services on filing and payment of the corporate income tax (CIT) and general consumption tax (GCT) for large taxpayers in Jamaica. We use a regression discontinuity design (RDD) that exploits an exogenous jump in the intensity of taxpayer service delivery, which occurs when a taxpayer reaches gross receipts of J$500 million (US$5.7 million) and is selected into the large taxpayer office (LTO). The results indicate null effects for the CIT but positive filing and payment compliance effects for the GCT. The contrasting results for the CIT and GCT may be due to the relatively weaker legal enforcement framework of the former. The results provide suggestive evidence of a complementarity between the strength of the legal enforcement framework of the taxing regime and the provision of taxpayer services. In the third essay we implement public goods messaging experiments to examine the effects on personal income tax (PIT) compliance among self-employed individuals in Jamaica. In the first sub-experiment we examine the effect of the standard public goods message on payment of quarterly PIT obligations. In the second sub-experiment we focus on payment of PIT arrears and expand the message context to include a variant of the standard public goods message – which provides additional information on actual spending on key public goods and services. The compliance outcomes in sub-experiment two relate to established PIT delinquencies, compared to sub-experiment one where there is no legal obligation to comply. We find that the standard public goods message had no effect on compliance with quarterly PIT payments in sub-experiment one. However results from sub-experiment two indicate positive compliance effects from the standard and augmented public goods messages on the probability of making a payment and the amount of PIT arrears paid after nineteen weeks. Point estimates from the standard and augmented public goods messages are not statistically different for any of the outcomes examined; suggesting that additional information on public spending allocations does not matter